Structure–function relationships of human JmjC oxygenases — demethylases versus hydroxylases. (December 2016) - Markolovic, Suzana; Leissing, Thomas M; Chowdhury, Rasheduzzaman; Wilkins, Sarah E; Lu, Xin; Schofield, Christopher J
Highlights: Human JmjC domain-containing proteins belong to the 2OG oxygenase superfamily. JmjC catalysis enables formation of stable alcohols or demethylation of N-methylated lysines. Several JmjC oxygenases have controversial functional assignments. Structural features that distinguish JmjC hydroxylases and demethylases are discussed. Non-catalytic domains, oligomerization, and active site differences are highlighted. Abstract : The Jumonji-C (JmjC) subfamily of 2-oxoglutarate (2OG)-dependent oxygenases are of biomedical interest because of their roles in the regulation of gene expression and protein biosynthesis. Human JmjC 2OG oxygenases catalyze oxidative modifications to give either chemically stable alcohol products, or in the case of N ɛ -methyl lysine demethylation, relatively unstable hemiaminals that fragment to give formaldehyde and the demethylated product. Recent work has yielded conflicting reports as to whether some JmjC oxygenases catalyze N-methyl group demethylation or hydroxylation reactions. We review JmjC oxygenase-catalyzed reactions within the context of structural knowledge, highlighting key differences between hydroxylases and demethylases, which have the potential to inform on the possible type(s) of reactions catalyzed by partially characterized or un-characterized JmjC oxygenases in humans and other organisms.